Surgical excision of umbilical endometriotic lesions with laparoscopic pelvic observation is the way to treat umbilical endometriosis. Issue 4 (November 2014) - Chikazawa, Kenro; Mitsushita, Junji; Netsu, Sachiho; Konno, Ryo
Abstract Primary umbilical endometriosis is extremely rare, although cases secondary to previous surgery have occasionally been reported. Here, we report three cases of umbilical endometriosis: two cases with previous cesarean section and one case of primary umbilical endometriosis. The treatment of choice for umbilical endometriosis is the excision of the lesions, and we believe laparoscopic pelvic observation is a beneficial addition, as 13%–15% of umbilical endometriosis cases are accompanied by pelvic endometriosis.